2023
DOI: 10.1038/s41598-023-28541-z
|View full text |Cite
|
Sign up to set email alerts
|

Substrate stiffness controls proinflammatory responses in human gingival fibroblasts

Abstract: Soft gingiva is often compromised in gingival health; however, the underlying biological mechanisms remain unknown. Extracellular matrix (ECM) stiffness is involved in the progression of various fibroblast-related inflammatory disorders via cellular mechanotransduction. Gingival stiffness might regulate cellular mechanotransduction-mediated proinflammatory responses in gingival fibroblasts. This in vitro study aims to investigate the effects of substrate stiffness on proinflammatory responses in human gingival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“… 31 During proliferation, these cell activities additionally change the microenvironment, which in turn may affect the cell responses, suggesting the potential involvement of a feedback loop. 32 34 In this study, an effect of stiffness on vaginal fibroblast behavior was possibly reflected in the cell morphologies, where an initially higher stiffness slightly increased spreading area on day 1. Furthermore, stiffer PIC-gels promoted fibroblast alignment and directionality, which can be explained by traction on fibroblast focal adhesions at an increased substrate stiffness.…”
Section: Discussionmentioning
confidence: 65%
“… 31 During proliferation, these cell activities additionally change the microenvironment, which in turn may affect the cell responses, suggesting the potential involvement of a feedback loop. 32 34 In this study, an effect of stiffness on vaginal fibroblast behavior was possibly reflected in the cell morphologies, where an initially higher stiffness slightly increased spreading area on day 1. Furthermore, stiffer PIC-gels promoted fibroblast alignment and directionality, which can be explained by traction on fibroblast focal adhesions at an increased substrate stiffness.…”
Section: Discussionmentioning
confidence: 65%
“…The stiffness of the local environment can tune cellular inflammatory responses through mechanotransduction [ 55 ]. When the hGFs were cultured on substrates with different stiffnesses (soft (5 kPa) or hard (25 kPa)), the expression of PTGES2 and IL-1β was significantly enhanced in the soft substrate group compared to that in the hard substrate group [ 56 ]. Cultured mouse monocytes with different substrate stiffnesses showed higher expression of Nos2 as stiffness increased [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results showing that the dual-cured resin cement with residual monomers induced inflammatory responses in the periodontal tissue cells are valuable for understanding the biological phenomenon around the margin of prostheses at a molecular level. On the other hand, the primary gingival fibroblasts from only one donor were used in this study because the primary cells from two donors, including those used in this study, showed similar inflammatory responses in the previous study [ 56 ]. However, the cells from multiple donors should be used in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these studies have focused on the differentiation of fibroblasts into myo-like, ECM-producing fibrotic phenotypes, little is known about how matrix stiffness may affect other fibroblast responses. In a recent report, oral cavity fibroblasts displayed lower expression of IL-1β when cultured on stiff matrix and a modest reduction in IL-6 and IL-1β expression in response to lipopolysaccharide when cultured in a hard matrix (Tiskratok;. However, the knowledge of the effects that the fibrotic ECM may have on the ability of fibroblasts to sustain homeostatic signals or undergo inflammatory differentiation remains limited and represents an interesting area for future investigation.…”
Section: Ecmmentioning
confidence: 99%